Bioactive components and beneficial bioactivities of flowers, stems, leaves of Lonicera japonica Thunberg: A review. (February 2023) - Li, Yuke; Xie, Long; Liu, Kai; Li, Xiaofang; Xie, Fan
Abstract: Introduction: Lonicerae japonicae flos (flowers or flower buds of Lonicera japonica Thunberg, called Jinyinhua, JYH in Chinese), together with Lonicerae japonicae caulis (stems of L. japonica, called Rendongteng, RDT in Chinese), is representatives of two edible-medicinal herbs from the same medicinal plant. Leaves of L. japonica, non-medicinal parts in China, have already been used medically with RDT in Japan and Korea, namely Lonicerae folium cum caulis. For a long history, research and applications of L. japonica mainly concentrated on JYH, while RDT and leaves are generally thought to have less medicinal properties than JYH. To the best of our knowledge, there is no review systematically comparing the three parts of L. japonica . In contrast, a gap exists in recognising the intersubstitution of JYH, RDT, leaves, or at least, their differences. Methods: The relevant information of flowers, stems and leaves was collected by scientific search engines including Elsevier, Google Scholar, Scifinder, CNKI (China national knowledge infrastructure), and Doctor's dissertations. Results: Based on our studies, the three showed remarkable homogeneity regarding major bioactive components, including caffeoylquinic and flavones. Differences in the content of chemical components may account for the discrepant intensities of anti-inflammatory, anti-microorganism, antioxidative activities of the three. In particular, leaves showed considerable activities, even more, active than JYH. Conclusions: Neither comparative investigations among JYH, RDT, leaves nor their activity differences at a molecular level have been systematically reviewed. Our study gains insights into elucidating the similarities and differences of efficacy among them. Highlights: To present similarities and differences among flowers, stems and leaves. Flowers, stems and leaves showed homogeneity regarding major components. Propose deficiencies on present studies.